Policy Constraints on Local Governance for Community Resilience: Qualitative Insights from Stakeholders in Disaster-prone Areas - Yuniarti, Y; Respati, T.; Januarita, R.; Irasanti, S. N. (KnE Social Sciences, 2024)
This qualitative study examines the impact of central government policies on community resilience for disaster preparedness, explicitly focusing on the constraints faced by local governments. This study explores the challenges hindering optimal performance at the local level through 18 informants using focus group discussions with key stakeholders, including sub-district heads and village leaders. The findings reveal that central government policies pose significant hurdles to local governance in disaster-prone areas. These policies restrict local governments’ decision-making authority and autonomy, impeding their ability to respond effectively to disaster risks and emergencies. Notably, the study highlights the presence of a communityled disaster management organization already in place, comprising members from within the community. The policy constraints identified include limited resource allocation, bureaucratic procedures, and a need for more flexibility in decision making. Stakeholders express concerns regarding rigid central government frameworks that do not recognize or account for the unique needs of individual communities. The study emphasizes the importance of policy reforms to empower and support local governments and their existing disaster management organizations. This research contributes to understanding community resilience by highlighting the vital role of local governance and community-led organizations in disaster preparedness. Keywords: community, disaster, government policies, resilience